Culture and pandemic control at cross-roads: navigating the burial guidelines for COVID-19-related deaths in a Ghanaian setting - Dorothy Takyiakwaa; Derek Anamaale Tuoyire; Susanna Aba Abraham; Elizabeth Ama Agyare; John Oti Amoah; Akosua Agyeiwaa Owusu-Sarpong; Kizito Omona; Dorcas Obiri-Yeboah; David Teye Doku (BMC, 2023)
Abstract Background Despite the large volume of scientific evidence on the rapid spread of the COVID-19 pandemic and associated high morbidity and mortality, little is known about the sociocultural disruptions which ensued. The current study explored the nuanced navigation of the COVID-19-related death and burial protocols and its impact on traditional burial and funeral rites in Ghana. Methods This qualitative study was based on the 'focused' ethnographic design. Data were collected using key informant interviews from nineteen COVID-19-related bereaved family members and public health officials involved in enforcing adherence to COVID-19-related death and burial protocols in the Cape Coast Metropolis of Central region of Ghana. Recursive analysis was conducted to generate the themes and sub-themes from the data. Results The overarching theme was "Uncultural" connotations ascribed to the COVID-19-related death and burial protocols. The COVID-19-related death and burial protocols were ubiquitously deemed by participants to be 'uncultural' as they inhibited deep-rooted indigenous and eschatological rites of separation between the living and the dead. This was fueled by limited awareness and knowledge about the COVID-19 burial protocols, resulting in fierce resistance by bereaved family members who demanded that public health officials release the bodies of their deceased relatives. Such resistance in the midst of resource limitation led to negotiated compromises of the COVID-19-related death and burial protocols between family members and public health officials. Conclusions Insensitivity to socio-cultural practices compromised the implementation of the COVID-19 pandemic control interventions, particularly, the COVID-19-related death and burial protocols. Some compromises that were not sanctioned by the protocols were reached to allow health officials and families respectfully bury their dead. These findings call for the need to prioritize the incorporation of sociocultural practices in future pandemic prevention and management strategies.